1961
DOI: 10.1002/cber.19610940834
|View full text |Cite
|
Sign up to set email alerts
|

Cyclische Diazoverbindungen, I. Herstellung und Umsetzungen von Diazirinen

Abstract: Die Isohydrazone des Cyclohexanons, Heptanons‐(4), Acetons und Acetophenons werden hergestellt. Sie lassen sich mit Silberoxyd zu Diazirinen dehydrieren, denen die von Curtius und von v. Pechmann für Diazoalkane angenommene Dreiringstruktur zukommt; in ihren Eigenschaften unterscheiden sie sich jedoch erheblich von den linearen Diazoalkanen. Sie können zu Isohydrazonen reduziert und mit Grignard‐Reagenz in alkylierte Diaziridine (Alkyl‐isohydrzone) übergeführt werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

1966
1966
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(45 citation statements)
references
References 14 publications
1
43
0
1
Order By: Relevance
“…The melting point of compound 3 (103 °C) coincided with that given in Ref. 6. 13 C NMR without proton decoupling (CDCl 3 ), δ: 24.4 (t, С(3), С(5), 1 J = 129.4 Hz); 24.6 (t, С(4), 1 J = 129.3 Hz); 35.7 (t, С(2), С(6), 1 J = 128.0 Hz); 56.9 (s, C(1), 2 J = 5.1 Hz).…”
Section: Methodssupporting
confidence: 55%
“…The melting point of compound 3 (103 °C) coincided with that given in Ref. 6. 13 C NMR without proton decoupling (CDCl 3 ), δ: 24.4 (t, С(3), С(5), 1 J = 129.4 Hz); 24.6 (t, С(4), 1 J = 129.3 Hz); 35.7 (t, С(2), С(6), 1 J = 128.0 Hz); 56.9 (s, C(1), 2 J = 5.1 Hz).…”
Section: Methodssupporting
confidence: 55%
“…Es wurden keine weiteren Versuche zur Isolierung des reinen Diarnins unternomrnen. (28): Eine Losung von 0.55 g (5 rnmol) 28 in 50 rnlO.1 N HCI wird in der oben beschriebenen Weise elektroreduziert. Cyclohexanon wurde gaschrornatographisch ermittelt.…”
Section: Ergebnisse Der Praparativen Elektroreduktion Einiger Hydraziunclassified
“…Decomposition of Phenylmethyldiazirine (4) Schmitz and Ohme (14) reported that the thermal decomposition of phenylmethyldiazirine 4 in nitrobenzene gave styrene. This is to be contrasted with Overberger and Anselme's results (15) for which they reported that the thermal decomposition of 1-phenyl-diazoethane 5 gave acetophenone azine as the only product.…”
Section: Decomposition Of Phenyl-n-butyldiazirine (1)mentioning
confidence: 99%
“…Synthesis of Phenylmethyldiazirine (4) Phenylmethyldiazirine, 4, was synthesized from the N-benzylmethylphenylketimine in the manner of Schmitz and Ohme (14). The final yield of diazirine (colorless) was 23%, based on the starting ketimine.…”
Section: Photolysis Of Phenyl-n-butyldiazirine (I) In Benzene;mentioning
confidence: 99%